Taxonomic novelties in Myrtaceae for Colombia - Carlos Parra Osorio; Ayda Patiño; Mónica Martínez; Mario Suárez (Caldasia)
A new species of Myrcia (Myrtaceae) from the subandean forests of the Nariño department, Colombia, is described and illustrated. Additionally, a new record of Eugenia (Myrtaceae) for the flora of the same region is identified. Taxonomic affinities of the new taxon are discussed, as well as unusual morphological characteristics of the fruit’s.